Role of Serum and Ultrasonometric Markers in the Early Diagnosis of Malignant Transformation of Periductal Liver Fibrosis in Patients with Opisthorchis Felineus Infection - A. Е. Kovshirina; O. S. Fedorova; Yu. V. Kovshirina; V. A. Petrov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Аim: to study the role of serum and ultrasonometric markers in the early diagnosis of malignant transformation of periductal fibrosis of the liver during the formation of cholangiocarcinoma against the background of chronic invasion of Opisthorchis felineus, in the population of endemic regions.Methods. A comprehensive one-stage comparative study was conducted in a case-control design, using the assessment of biochemical parameters (lactate, alanine aminotransferase, aspartate aminotransferase, gamma-glutamyl transpeptidase, alkaline phosphatase, glucose, direct and indirect bilirubin, high-density lipoproteins and low-density lipoproteins, triglycerides, urea and total protein), immunological parameters (transforming growth factor beta) and tumor markers (CA 19-9, СYFRA 21-1) in blood serum samples obtained from patients with O. felineus infection, with and without periductal fibrosis, O. felineus-infected patients with cholangiocarcinoma and representatives of control groups. During the analytical stage, the relationship between the structural features of the liver ac- cording to the results of ultrasound examination (presence of opisthorchiasis-associated periductal fibrosis), clinical parameters, parasitological study data (infection intensity), and changes in biochemical, immunological parameters and tumor markers in patients against the background of O. felineus infection was assessed. Statistical analysis was performed using the R programming language (version 3.6.1).Results. Evaluation of the relationship between the presence of ultrasound signs of stage 1–2 opisthorchiasis-associated periductal fibrosis and changes in serum levels of the biochemical, immunologic parameters and oncomarkers in patients with O. felineus infection demonstrated that the levels of alkaline phosphatase, conjugated bilirubin, AST, glucose and CA 19-9 oncomarker were significantly higher in the serum of patients in the group with cholangio-carcinoma and opisthorchiasis (p < 0.01).Conclusion. The first pilot data on the relationship between ultrasonometric signs of periductal liver fibrosis and the increase of CA 19-9 oncomarker as well as biochemical parameters (alkaline phosphatase, direct bilirubin, aspartate aminotransferase, glucose), which can be used for early diagnosis of malignant transformation of periductal liver fibrosis with the formation of cholangiocarcinoma in O. felineus-infected population in endemic regions, were obtained.